RFID Implementation for Material Safety at Storage Area in Construction Site - Hairizan, Mohamad Amirul Hakim; Kasim, Narimah; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun; Dodo, Mansir (Research in Management of Technology and Business, 2023)
Malaysia's construction industry is impacted by material safety issues as a result of poor safety management, lack of standardization, and insufficient technology. Radio Frequency Identification (RFID) is currently being used in a variety of industries, including manufacturing, health care, transportation, and tracking applications, particularly in supply chain management.  However, RFID has not been widely used in the construction industry specifically for materials safety in storage areas. Therefore, the objectives of the research are to identify the potential, factors, and steps to promote RFID implementation for material safety in the storage area at the construction site. To achieve the objectives, the research was conducted using quantitative methods for primary data collection and questionnaires as the instrument used to collect the data. There were 254 respondents among G7 contractors selected at Johor state to obtain information for this research. The data were analyzed through SPSS software to determine the mean and standard deviation. Furthermore, Microsoft Excel generates pie charts, bars, frequency, and percentage values for the respondents’ backgrounds. The results showed that RFID had the potential to track activities and eliminate human error. The influencing factors to implement RFID is efficient delivery of materials and an anti-theft system. In addition, the steps to promote RFID implementation in material safety were to require RFID technology promotion by top management support. In conclusion, the research provided a great deal of knowledge for effective safety management with RFID implementation for material safety at the construction site.